2018
DOI: 10.3390/app8122619
|View full text |Cite
|
Sign up to set email alerts
|

Stress Concentration and Optimized Analysis of an Arbitrarily Shaped Hole with a Graded Layer under Anti-Plane Shear

Abstract: This paper provides a general solution to the anti-plane problem of an arbitrarily shaped hole reinforced with a functionally graded (FG) layer in a homogenous plate. By using the piece-wise homogeneous layers method and the conformal mapping technique, the complex potentials in the form of series in the FG layer are derived based on the theory of complex variable functions. The influence of the FG layer on the shear stress distributions around some typically shaped holes are discussed by numerical examples, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Applying strain to a substrate with a circular hole (hole sample) can produce a high-stress region at the edge of the circular hole perpendicular to the loading direction . A hole sample is useful in evaluating the stress concentration around a circular hole . Simulated von Mises images show nonuniform stress distributions on the PDMS sheet with a circular hole (hole PDMS sheet) (Figures a and S9).…”
Section: Resultsmentioning
confidence: 99%
“…Applying strain to a substrate with a circular hole (hole sample) can produce a high-stress region at the edge of the circular hole perpendicular to the loading direction . A hole sample is useful in evaluating the stress concentration around a circular hole . Simulated von Mises images show nonuniform stress distributions on the PDMS sheet with a circular hole (hole PDMS sheet) (Figures a and S9).…”
Section: Resultsmentioning
confidence: 99%
“…The stress distribution around the holes has been extensively studied by analytical methods [4,5], finite element methods (FEM) [6], and experimental methods [7][8][9]. Guan et al [10] introduced a general shear-stress solution to the anti-plane problem of an arbitrarily shaped hole that was reinforced with a functionally graded layer in a homogenous plate. Shang et al [11] investigated the high-temperature tensile behavior for film-hole plates and found that the strain distribution obtained in situ by the digital image correlation technique exhibits an X-like concentration around the hole.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the theoretical predictions agree well with the experimental results. The analytical methods mainly utilize the theory of complex variable functions and the conformal mapping technique to obtain the stress distribution of a rectangular or infinite plate with holes [10]. It may be insufficient to deal with the holes with complex shapes or particular positions in practical engineering structures with advanced materials [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi [27] presented an analytical solution of the elastic stress fields around a circular elastic inclusion in a radial FGM plate under a uniform anti-plane shear loading at infinity. Guan and Li [28] analyzed the stress concentration around an arbitrarily shaped hole reinforced with an FGM layer in an infinite plate under anti-plane shear and performed the optimized analysis of the SCF. The above works are mainly for anti-plane problems.…”
Section: Introductionmentioning
confidence: 99%